Keys to Successful Reading - Stephenson, Eleanor A.; Southeast Arkansas Educational Service Center, Monticello ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
One facet in the development of a good program of reading is conscientious planning. The use of behaviorally stated objectives developed on a weekly, monthly, and unit basis provides the teacher with a means for measurable and meaningful evaluation. Individual diagnosis enables the teacher to know the level of instruction at which to begin a child and the specific reading skills he needs. Informal inventories, diagnostic tests, intelligence tests, ear and eye tests, and interest inventories are meaningful tools to employ at this stage of a reading program. Reading materials should be of varied interests and difficulty levels. This could include several sets of basal readers, supplementary materials, and multi-media materials. With this wide variety of materials a teacher can choose those that are appropriate to the level of each child. Meaningful reinforcement procedures are of high importance in a successful reading program. The most effective reinforcements appear to be those directed toward the positive aspects of a program. A continuous evaluation based on objectives constitutes the final major phase of a reading program. The effectiveness of a program should be measured through an evaluation of the child's progress in relation to the objectives written for that child. (WR)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavioral Objectives; Reading; Reading Diagnosis; Reading Improvement; Reading Instruction; Reading Materials; Reading Programs; Reading Skills; Reading Tests